Writing Knowledge and Writing Performance of Undergraduate Students - Indra Perdana; Joni Bungai; Wardani Dwi Wihastyanang; Ralph Hery Budhiono; Valentina Lovina Tanate (International Journal of Language Education, 2023)
This paper describes an investigation about the relationship between students' writing knowledge and second language writing performance. Metacognitive and metalinguistic knowledge contribute significantly to writing performance. As a foreign language, 78 undergraduate students took a writing knowledge class and a writing proficiency test. The knowledge process has a strong influence on writing performance. Except for vocabulary knowledge, other aspects and sub-aspects had no significant effect on writing performance. Vocabulary knowledge had a negative impact on writing performance. In other words, while some aspects and sub-aspects of writing knowledge did not significantly influence writing performance, others did. The pedagogical implication is that all aspects of writing knowledge must be explicitly taught in writing instruction in order to improve students' writing quality. However, there must be a priority of aspect as the core of the material to be taught, with the other aspects and sub-aspects serving as complementary materials. This could result in a moderate relationship finding and a low percentage of contribution. Undergraduate English as a Foreign Language students from various institutions and provinces may have varying levels of language proficiency and writing skills.